(untitled) (Modern education and development, 2025)
Database architecture plays a critical role in the design and management of modern database systems. It provides the framework for organizing, storing, and retrieving data efficiently. The application of database architecture is crucial in ensuring the scalability, performance, and security of data storage systems. This article explores the fundamental concepts of database architecture, including its components such as data models, schemas, and storage structures. It also examines how different types of database architectures—such as hierarchical, relational, object-oriented, and distributed databases—are applied in various sectors, from business to healthcare, e-commerce, and cloud computing. The paper further discusses the role of database architecture in handling large volumes of data, ensuring data integrity, and supporting the growing demand for real-time processing. Finally, it addresses challenges and emerging trends in database architecture, such as the move toward cloud-based solutions and the integration of artificial intelligence to optimize database management.